2018
DOI: 10.1080/01616412.2018.1462752
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association between sexual dysfunction and demyelinating plaque location and number in female multiple sclerosis patients

Abstract: Purpose To investigate the frequency of sexual dysfunction (SD) in female multiple sclerosis (MS) patients and to explore its association with the location and number of demyelinating lesions. Material and Methods We evaluated 42 female patients and 41 healthy subjects. All patients underwent neurological examination and 1.5 T brain and full spinal MRI. All subjects completed the female sexual function index (FSFI), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Short-Form 36 Quality of Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Different patient characteristics were found to be associated with SD including advancing age, lower educational level, and poor QoL . MS‐related parameters found to be associated with SD were longer disease duration, progressive MS, greater neurological disability, worse physical functions, fatigue, urinary problem, and poor cognitive function .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Different patient characteristics were found to be associated with SD including advancing age, lower educational level, and poor QoL . MS‐related parameters found to be associated with SD were longer disease duration, progressive MS, greater neurological disability, worse physical functions, fatigue, urinary problem, and poor cognitive function .…”
Section: Discussionmentioning
confidence: 98%
“…Results of case-control studies (n = 14): The prevalence of SD in women with MS was reported to be 34.9% to 95% (n = 8 studies). In these studies, SD rates were reported to be higher in PwMS compared to healthy control [45][46][47][48][49][50][51][52][53] and the difference was found to be statistically significant in eight studies [45][46][47][48][49][50][51]53 (Table S1). No significant differences in prevalence were seen compared with other chronic neurological disorders (migraine).…”
Section: Prevalence and Symptomatology Of Sdmentioning
confidence: 99%
“…The presented tool is characterised by high credibility and is often used in research on women’s sexuality around the world. Very diverse groups of women take part in these studies, for example patients with multiple sclerosis [22], hyperthyroidism [23], overweight [24], suffering from neoplastic diseases [25], or endometriosis [26]. In addition, the questionnaire is adaptable enough for use among women of varying stages of sexual development, from the pre- to post-menopausal periods [27].…”
Section: Introductionmentioning
confidence: 99%
“…9 Primary sexual dysfunction in MS is caused by MS-related neurologic changes in the central nervous system, such as damage in the brain, in the spinal cord areas, and in the peripheral neurons engaged in sexual response. [10][11][12] Female primary sexual dysfunction in MS includes reduced libido (up to 85%), difficulties in achieving orgasm (up to 73%), reduced lubrication (up to 47%), changes in vaginal sensation (up to 30%), and anorgasmia (29%). 7 Primary sexual dysfunction in men with MS mainly refers to reduced libido (up to 70%), incomplete or total loss of erectile functions (up to 67%), and inability to ejaculate or premature ejaculation (up to 52%).…”
Section: Sexual Dysfunction In Ms and Its Treatmentmentioning
confidence: 99%